Ответы и объяснения

2013-12-06T13:17:04+04:00
Используем основное тригонометрическое тождество:
cos^2(x) + sin^2(x) = 1
Интеграл ( dx / (sin(x)*cos(x)) ) = Интеграл ( 1*dx / (sin(x)*cos(x)) ) = Интеграл ( ( cos^2(x) + sin^2(x) )*dx / (sin(x)*cos(x)) ) = Интеграл ( cos^2(x)*dx / (sin(x)*cos(x)) ) + Интеграл ( sin^2(x)*dx / (sin(x)*cos(x)) ) = Интеграл ( cos(x)*dx / sin(x) ) + Интеграл ( sin(x)*dx / cos(x) ) = Интеграл ( d(sin(x)) / sin(x) ) + Интеграл ( -d(cos(x)) / cos(x) ) =
ln (sin(x)) - ln(cos(x)) + C = ln (tg(x)) + C